Reducing computational costs by compressing the structural description in image classification methods - Gorokhovatskyi, Volodymyr; Chmutov, Yurii; Tvoroshenko, Iryna; Kobylin, Oleg (Національний технічний університет "Харківський політехнічний інститут", 2025)
The research of the article is focused on ways to reduce the amount of analyzed data when applying image classification methods in computer vision systems. The aim of this work is to develop approaches to reduce the dimensionality of the vector description of the etalon base using metric granulation, which reduces computational costs and speeds up the classification process while maintaining a sufficient level of accuracy. Methods used: keypoint descriptors, metric data granulation apparatus, image classification and processing theory, data structures, software modeling. Results: the formalism of granular representation was developed; experimental modeling was carried out using five-level granulation, which reduced the time spent tenfold while maintaining high classification accuracy. In the comparative aspect, we studied ways to reduce the volume of vector descriptions based on data discarding, and researched the effect of the granularity level on the accuracy and classification time.

Дослідження статті зосереджені на способах скорочення обсягу аналізованих даних при застосуванні методів класифікації зображень у системах комп'ютерного зору. Мета – розвинення підходів щодо скорочення розмірності векторного опису бази еталонів за допомогою метричної грануляції, що знижує обчислювальні витрати та прискорює процес класифікації при збереженні достатнього рівня точності. Застосовувані методи: дескриптори ключових точок, апарат метричної грануляції даних, теорія класифікації та обробки зображень, структури даних, програмне моделювання. Отримані результати: розроблено формалізм гранульованого подання, здійснено експериментальне моделювання з використанням п'ятирівневої грануляції, що скоротило часові витрати у десятки разів при збереженні високої точності класифікації. У порівняльному аспекті вивчено способи скорочення обсягу векторних описів на підставі відкидання даних, досліджено вплив рівня грануляції на точність та час класифікації.
Зниження обсягу обчислювальних затрат шляхом стиснення структурного опису у методах класифікації зображень
Keywords: classification speed; data rejection; description reduction; granularity; image classification; keypoint descriptors; швидкодія класифікації; відкидання даних; скорочення опису; грануляція; класифікація зображень; дескриптори ключових точок